ANALISIS PENERAPAN READING CAMP TERHADAP LITERASI MEMBACA SISWA DI KELAS IV SDN 2 FONTEIN KOTA KUPANG - Happu, Inriyani Tarru; Nitte, Yulsy Marselina; Mbuik, Heryon Bernard (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low reading literacy of elementary school students is still a major problem in the world of education, especially in Kupang City which based on the results of the National Assessment is still below the minimum competence. One of the efforts made to improve reading literacy is through the implementation of the Reading Camp program. This study aims to describe the application of Reading Camp in improving reading literacy of grade IV students at SDN 2 Fontein, Kupang City and identify the impacts and obstacles faced during its implementation. This study uses a qualitative approach with a descriptive type of research. The research subjects consisted of grade IV teachers, principals, and six students. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Data analysis was carried out using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The results of the study showed that the implementation of Reading Camp was carried out on a scheduled basis twice a week with independent reading, reading together, discussions, retelling the content of reading, and creative expression. This program has a positive impact on increasing interest and motivation in reading, students' courage in communicating, and understanding of reading content. However, there are several obstacles in its implementation, including limited variations in reading books, inadequate supporting facilities, and differences in students' reading abilities. Overall, Reading Camp can be an effective and contextual literacy strategy in improving the reading literacy of elementary school students.